Control Strategies for Steer-By-Wire Systems: An Overview - Muhammad Arjuna Putra Perdana; Alexander C. Budiman; Rina Ristiana; Aam Muharam; Kristian Ismail; Muhammad Redho Kurnia; Amin; Naili Huda; Sunarto Kaleg; Abdul Hapid (Technologies)
Steer-by-wire (SbW) is the latest steering evolution, providing many benefits, such as reduced vehicle weight and enhanced steering capability. While reliability is one of the main concerns hindering its widespread application, the potential of this technology to revolutionize the automotive industry is huge. Control techniques play an important part in achieving the full potential of SbW by focusing on the development of its performance and safety aspects. This paper provides a review of the control techniques that are being used in SbW technology to achieve better performance and enhance safety. Various control techniques for SbW exist to serve different purposes when dealing with the non-linear nature of the SbW dynamics. Although there is no one-size-fits-all control technique for all the requirements of the SbW, this study highlights that the non-linear controllers based on the sliding mode control (SMC) are a popular option for enhancing the accuracy of SbW systems. However, these controllers often suffer from a downside known as chattering. In contrast, robust controllers like Model Predictive Controllers (MPCs) can effectively manage uncertain dynamics and eliminate chattering, although they pose challenges due to their high computational costs.